2021
DOI: 10.3390/ijms222112011
|View full text |Cite
|
Sign up to set email alerts
|

Functional Identification of Complement Factor D and Analysis of Its Expression during GCRV Infection in Grass Carp (Ctenopharyngodon idella)

Abstract: Complement factor D (Df) is a serine protease well known for activating the alternative pathway (AP) in mammals by promoting the cleavage of complement component 3 (C3), thus becoming involved in innate defense. In teleost fish, however, the functional mechanisms of Df in the AP and against pathogen infection are far from clear. In the present study, we cloned and characterized the Df gene, CiDf, from grass carp (Ctenopharyngodon idella) and analyzed its function in promoting C3 cleavage and expression changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…The results showed that the content of CiCFI proteins continued to decline during GCRV infection from the early stage at the incubation period to the late stage at the restored period, corresponding to the results from the liver. In contrast, our previous study has revealed that Df, a well-known complement enhancer in the AP by cleaving Bf to promote the cleavage of C3 and the production of C3b, is observed with a continued up-regulated expression in the grass carp during GCRV infection, even at the late stage of infection [ 35 ]. Theoretically, the down-regulation of CFI and the up-regulation of Df should bring about an increase in the content of C3b proteins in the serum of grass carp during GCRV infection.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The results showed that the content of CiCFI proteins continued to decline during GCRV infection from the early stage at the incubation period to the late stage at the restored period, corresponding to the results from the liver. In contrast, our previous study has revealed that Df, a well-known complement enhancer in the AP by cleaving Bf to promote the cleavage of C3 and the production of C3b, is observed with a continued up-regulated expression in the grass carp during GCRV infection, even at the late stage of infection [ 35 ]. Theoretically, the down-regulation of CFI and the up-regulation of Df should bring about an increase in the content of C3b proteins in the serum of grass carp during GCRV infection.…”
Section: Discussionmentioning
confidence: 89%
“…In our previous study, transcriptome analyses show that the AP is significantly activated in grass carps after GCRV infection, with 2.18-fold up-regulation of Df mRNA expression and 9410.14-fold down-regulation of CFI mRNA expression [ 33 ]. Df, a complement enhancer, involves the initiation and amplification loops of complement system activation by cleaving Bf to promote C3 cleavage, and its regulation on complement activation has recently been verified in the grass carp [ 35 ]. CFI, a serine protease, is well-known as the key complement inhibitor, and plays a crucial role in host-pathogen interactions in mammals [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, it seems that most of the complement components other than FD have appeared after the duplication of primordial genes encoding C3/C4/C5, FB/C2, C1r/C1s/MASP‐1/MASP‐2/MASP‐3, and C6/C7/C8/C9 molecules 69,75 . Since FD has not been identified in lampreys and cartilaginous fish, teleost fish seems to be the first species in which FD appeared 76 . The exact role of FD in the complement system of teleost fish is unclear.…”
Section: Evolution Of Masp‐3 and Fdmentioning
confidence: 99%
“…69,75 Since FD has not been identified in lampreys and cartilaginous fish, teleost fish seems to be the first species in which FD appeared. 76 The exact role of FD in the complement system of teleost fish is unclear. However, the incubation of recombinant grass carp FD with grass carp serum significantly increased the C3b content, suggesting that at least FD is involved in promoting C3 cleavage in grass carp, likely via AP activation.…”
Section: E Voluti On Of Ma S P-3 and Fdmentioning
confidence: 99%